Identification and in vitro reactivity of celiac immunoactive peptides in an apparent gluten-free beer. - Ana Real (Public Library of Science (PLoS), 2014)
Gluten content from barley, rye, wheat and in certain oat varieties, must be avoid in individuals with celiac disease. In most of the Western countries, the level of gluten content in food to be considered as gluten-free products is below 20 parts per million measured by ELISA based on specific anti-gluten peptide antibody. However, in beverages or food suffering complex hydrolytic processes as beers, the relative proportion of reactive peptides for celiac patients and the analytical techniques may differ, because of the diversity of the resulting peptide populations after fermentations. A beer below 20 parts per million of gluten but yet detectable levels of gluten peptides by anti-gliadin 33-mer antibodies (G12 and A1) was analyzed. We identified and characterized the relevant peptides for either antibody recognition or immunoactivity in celiac patients. The beer was fractionated by HPLC. The relative reactivity of the different HPLC fractions to the G12/A1 antibodies correlated to the reactivity of peripheral blood mononuclear cells isolated from 14 celiac individuals. Peptides from representative fractions classified according to the relative reactivity to G12/A1 antibodies were identified by mass spectrometry. The beer peptides containing sequences with similarity to those of previously described G12 and A1 epitopes were synthesized and confirmed significant reactivity for the antibodies. The most reactive peptides for G12/A1 also confirmed the highest immunogenicity by peripheral blood mononuclear cell activation and interferon γ production from celiac patients. We concluded that preparative HPLC combined with anti-gliadin 33-mer G12/A1 antibodies were very sensitive and specific methods to analyze the relevant immunogenic peptides in hydrolyzed gluten.